Association of miR-181c/d gene locus rs8108402 C/T polymorphism with susceptibility to Kawasaki disease in Chinese children - Yao, Meiqing; He, Qin; Yang, Manqiong; Wu, Zhixiang; Li, Ying; Kong, Min; Kang, Zhijuan; Yi, Lu; Hu, Yanan; Huang, Lihua; Li, Zhuoying; Yang, Zuocheng (Frontiers in Pediatrics, 2022)
ABSTRACT Background: Kawasaki disease (KD) is an acute systemic vasculitis of unknown etiology. The rs8108402 C/T single nucleotide polymorphism (SNP) is located in the promoter region of miR-181-c/d and the intron of Nanos 3. The miR-181 family contributes to the pathogenesis of cardiovascular and inflammatory disorders, while Nanos 3 is involved in DNA transcription regulation and cell proliferation. However, no studies have examined the association between miR-181c/d and Nanos 3 polymorphisms and the susceptibility and development of KD. Objective: The purpose of our study was to examine the association of miR-181c/miR-181d/Nanos 3 gene locus rs8108402 C/T polymorphism with KD and the development of coronary artery lesions (CAL). Methods: Peripheral blood specimens from 100 children with KD and 100 healthy children were collected. The locus rs8108402 C/T of miR-181c/d gene polymorphism was detected using polymerase chain reaction-sequencing-based typing technique. Results: There were statistically significant differences in C and T allele frequency distributions between the KD group and healthy controls for the polymorphic site rs8108402 C/T (P=0.002). Moreover, the distribution of the genotypes CC, CT, and TT also showed statistical difference between the KD and control groups (P=0.003). Compared to the rs8108402 C allele, the T allele was significantly associated with increased KD susceptibility (OR=2.080, 95% CI=1.317~3.283). However, there were no significant associations discovered between the rs8108402 C/T polymorphism and CAL formation risk in the KD group. Conclusion: SNP rs8108402 C/T located in the miR-181c/d promoter and Nanos3 intronic region is associated with susceptibility to Kawasaki disease in Chinese children, but not associated with the development of coronary artery lesions in the same population. Keywords: Kawasaki disease; miR-181; Nanos3; coronary artery lesions; single-nucleotide polymorphisms